Stocks of carbon in logs and timber products from forest management in the southwestern amazon - Romero, Flora Magdaline Benitez; Jacovine, Laércio Antônio Gonçalves; Ribeiro, Sabina Cerruto; Neto, José Ambrósio Ferreira; Ferrante, Lucas; da Rocha, Samuel José Silva Soares; Torres, Carlos Moreira Miquelino Eleto; de Morais Junior, Vicente Toledo Machado; Gaspar, Ricardo de Oliveira; Velasquez, Santiago Ivan Sagredo; Vidal, Edson José; Staudhammer, Christina Lynn; et al. (Forests, 2020)
Amazon forest management plans have a variety of effects on carbon emissions, both positive and negative. All of these effects need to be quantified to assess the role of this land use in climate change. Here, we contribute to this effort by evaluating the carbon stocks in logs and timber products from an area under forest management in the southeastern portion of Acre State, Brazil. One hundred and thirty-six trees of 12 species had DBH ranging from 50.9 cm to 149.9 cm. Basic wood density ranged from 0.3 cm-3 to 0.8 g cm-3 with an average of 0.6 g cm-3. The logs had a total volume of 925.2 m3, biomass of 564 Mg, and carbon stock of 484.2 MgC. The average volumetric yield coefficient (VYC) was 52.3% and the carbon yield coefficient (CYC) was 53.2% for logs of the 12 species. The sawn-wood products had a total volume of 484.2 m3, biomass of 302.6 Mg, and carbon stock of 149.9 MgC. Contributions of the different species to the total carbon stored in sawn-wood products ranged from 2.2% to 21.0%. Means and standard deviations for carbon transferred to sawn-wood products per-species from the 1252.8-ha harvested area ranged from 0.4 ± 1.1 MgC to 2.9 ± 0.4 MgC, with the largest percentages of the total carbon stored in wood products being from Dipteryx odorata (21.0%), Apuleia leiocarpa (18.7%), and Eschweilera grandiflora (11.7%). A total of 44, 783 pieces of sawn lumber (such as rafters, planks, boards, battens, beams, and small beams) was obtained from logs derived from these trees. Lumber production was highest for boards (54.6% of volume, 47.4% of carbon) and lowest for small beams (1.9% of volume, 2.3% of carbon). The conversion factor for transforming log volume into carbon stored in sawn-wood products was 16.2%. Our results also show that species that retain low amounts of carbon should be allowed to remain in the forest, thereby avoiding low sawmill yield (and consequent generation of waste) and allowing these trees to continue fulfilling environmental functions. © 2020 by the authors.
Keywords: Carbon yield coefficient; Climate Change; Forest Management; Sawmill; Volumetric yield coefficient; Wood sawing